The impact of debates as a teaching strategy in the classroom to medical students / Farah Ayuni Ramlan ... [et al.] - Ramlan, Farah Ayuni; Kassim, Nilam Maisarah; Pakirisamy, Saminathan; Selvakumar, Vishalini (2016)
Teaching strategies and methodologies have evolved over time and according to the needs of learners and the changing teaching-learning environment. Debates, particularly academic debates are considered as one of the many active learning strategies to motivate students. The preparation, presentation, defence, class participation and peer-interaction during a well organised debate can provide ample language practice for the student. Thus, it is an interesting area to be explored for its effectiveness as a teaching strategy. The objectives of this paper are to identify students' perception on using debates in the classrooms and to identify the impact of implementing debates as a teaching strategy for medical undergraduates. A survey on the topic was conducted among medical undergraduates in a private medical college in Ipoh. The results show that taking part in debates enhances students' level of confidence through their active involvement in the process of conducting and participating in a debate.